Conceptualizing African migration to South-East Asia: student, trader, businessman & future of policy in Malaysia - Ansah, Eric Schubert (Penerbit Universiti Kebangsaan Malaysia, 2016)
This article is based on the results of a two-year research project on African migration to Southeast Asia, namely Malaysia and Singapore, at the Institute of Ethnic Studies (KITA), the National University of Malaysia. It was conducted from 2011-2013 and followed-up with online interviews of respondents from 2014 till the end of 2015. The purpose of the research project entitled, “African Migration to Southeast Asia: Characteristics, Impact and Future of Policy”, was to highlight the character, specificities, policy contexts and outcomes of African migration to Southeast Asia. African migration to both East and Southeast Asia is relatively new and unknown compared to the older and more established Eurocentric migration of Africans to Europe and West. As the African presence continues to grow while the inner dynamics of this new migration appear hidden, it has puzzled policy-makers and bureaucrats alike, caused consternation, outrage and is experienced as a sceptre of invasion among the local populations. It is argued that the new African migration is to be understood as constituted by a self-regulatory process of African migrants comprised of relations among logics of migration, socio-economic networks, institutions and a set of State policies across domains. While transnational institutional change, including ‘look East’ policies of African States, the changing climate for migration in Europe and Malaysia’s vision to become a high-income country by 2020, are among the permissive causes, it is the actual social relations of African migrants in a particular location which shape migration outcomes. As can be observed empirically and argued, African migration to Southeast is increasingly similar to Chinese migrations in the global context. Hence African migration to Malaysia may be seen in terms of the dynamics, social relations, institutions and transactions of overseas Chinese and transnational Chinese studies. The future of policy in Malaysia, as across Southeast Asia may be understood as the relationship of developmental States to the self-regulatory process of African migrants and emergence of Africa-town, with Chinese characteristics.